Intervenções no ambiente escolar visando a promoção da saúde - Rodrigues, Carolina Braz Carlan (2020)
The present study was developed in a public school in the state network of Santa Maria / RS and aimed to analyze the contributions of actions mediated by interdisciplinary projects, aiming at health promotion, in the determinants of health and lifestyle of schoolchildren, of the final years of elementary education. The work is characterized by its nature: qualitative and quantitative, the objectives: descriptive and explanatory, the procedures: case study, the place: field and the type of study: longitudinal. Over four years (2011, 2012, 2013 and 2014) continuous training was developed with teachers, with the aim that the knowledge built and worked in the classroom reflected in the habits and lifestyles of schoolchildren in the final years of teaching. fundamental. For follow-up, anthropometric assessments, semi-structured questionnaires, interviews, participant observation and researchers' records in the field diary were performed. The results are presented in two article and one manuscript. The first article describes the interdisciplinary pedagogical projects, developed by the school's educators, and under a critical interpretation, the projects were structured from the perspective of the Three Pedagogical Moments, in order to identify the contributions of this dynamic to the process of elaborating the activities developed in the classroom. Potentialities for collective construction and interdisciplinarity in actions aimed at health promotion, as well as the use of the Three Pedagogical Moments as a didactic-pedagogical alternative, were highlighted. The second article analyzes the contributions of interventions in the school environment, aiming at health promotion, health determinants and lifestyle in schoolchildren. In particular, it verifies the impacts of these interventions on the levels of physical activity, nutritional status, nutritional knowledge, eating habits and body image. Significant consistent changes, over time, were observed in the aspects investigated. The proposal for interventions in the school context presented and enabled the approach of themes related to health promotion in the classroom. The manuscript investigated whether the pedagogical actions aimed at health education were able to change aspects of physical activity, nutritional status, nutritional knowledge, eating habits and body image of the students. The results showed that the subjects involved in this study experienced behavioral changes. However, for actions in the school environment to be carried out effectively, it is necessary that there is commitment from all involved. It is concluded that interventions in the school environment, aiming at health promotion should be widely discussed and developed, so that strategies, actions and activities aimed at improving students' health, contribute to a behavioral change. However, it stands out on the relevance of the permanence of the group of researchers in the school, and the benefits of this partnership. Finally, a limitation was identified as to the involvement and participation of parents / guardians in the educational processes developed at school, which are essential for the training of students, as well as for the collective construction of knowledge and attitudes about a healthier life.